Hinotori Surgical Robot System, a novel robot‐assisted surgical platform: Preclinical and clinical evaluation. (18th July 2022) - Hinata, Nobuyuki; Yamaguchi, Raizo; Kusuhara, Yoshito; Kanayama, Hiroomi; Kohjimoto, Yasuo; Hara, Isao; Fujisawa, Masato
Abstract : Objectives: To evaluate the safety and efficacy of the hinotori™ Surgical Robot System in preclinical and clinical studies. Methods: Preclinical studies on 10 living female porcine and four fresh male cadavers were conducted. Different types of urologic surgical procedures were performed by experienced urological surgeons using the hinotori system: partial nephrectomy, vesicourethral anastomosis, and pelvic lymph node dissection in porcine, and partial nephrectomy, radical prostatectomy, and pelvic lymph node dissection in cadavers. In a multi‐institutional single‐arm clinical study, radical prostatectomy was performed in 30 patients with localized prostate cancer to evaluate safety outcomes. The primary endpoint was safety profiles, including device errors and perioperative complications, and the secondary endpoints were console time, blood loss, and positive surgical margin rate. Results: The preclinical results were similar to those reported for the daVinci surgical system. The performance of the hinotori was equivalent to that of the daVinci surgical system, based on a global assessment by the surgeons. Safety was confirmed in a first‐in‐human clinical study of robot‐assisted radical prostatectomy using hinotori in 30 patients. The procedures were completed as planned in all cases, and three (10%) perioperative adverse events were observed. Conclusions: The safety of the newly developed hinotori surgical system was shown in the present preclinical and clinical studies. Further studies are required to confirm its clinical efficacy.